Bionanomedicine: A “Panacea” In Medicine? - Anurogo, Dito; Parikesit, Arli A; Ikrar, Taruna (UI Scholars Hub, 2017)
Recent advances in nanotechnology, biotechnology, bioinformatics, and materials science have prompted novel developments in the field of nanomedicine. Enhancements in the theranostics, computational information, and management of diseases/disorders are desperately required. It may now be conceivable to accomplish checked improvements in both of these areas utilising nanomedicine. This scientific and concise review concentrates on the fundamentals and potential of nanomedicine, particularly nanoparticles and their advantages, nanoparticles for siRNA conveyance, nanopores, nanodots, nanotheragnostics, nanodrugs and targeting mechanisms, and aptamer nanomedicine. The combination of various scientific fields is quickening these improvements, and these interdisciplinary endeavours to have significant progressively outstretching influences on different fields of research. The capacities of nanomedicine are immense, and nanotechnology could give medicine a completely new standpoint.